Las obligaciones tributarias y el nivel de cumplimiento de los comerciantes formales con el gobierno autonomo descentralizado municipal de San Jacinto de Buena Fe año 2012 - Mendoza Zambrano, Isabel Concepción (2015)
This research is to determine the level of compliance with tax obligations formal Canton Merchants good faith with the Decentralized Autonomous Municipal Government of San Jacinto de Buena Fe, located at Av. Principal August 7, diagonal to the central park, where there is much of traders who do not meet their payments to the Municipal GAD, such as tuition, patent and tax of 1.5 per thousand of the total assets. Budget by Decree of 2012, it can be seen that taxes raised enrollments less than the initial allocation, is that in 2011 a value of 15,000.00 was obtained and in 2012 a value was obtained to 10899.67, while the tax of the Commercial Patent higher value than the projection for the year 2011, a total of 70,000 and for 2012 a total of 113,976.65 and finally was raised in the Tax of Total Assets decreased value of the previous year, is for 2011 revenue was 22,000.00 was obtained, while in 2012 income had a total tax payment 10.839,55.En Enrollment 32 businesses have canceled their business obligations and 84 no, that is, a 27.59% has fulfilled its tax liability, while a 72.41% has not done. Payment of Patent Tax, canceled 39 shops in the department of Revenue and 77 did not, which means a 33.62% paid their commitment and 66.38% did not. Tax payment of 1.5 per thousand of Total Assets 17 stores credited its obligations Decentralized Autonomous Government of San Jacinto de Buena Fe and 99 are not current in paying taxes. From which it follows that 14.66% complied with the payment of this tax, and that 85.34% have not done so. The research that I was used is Bibliographical and field, plus inductive and deductive methods which allowed more accurate information from taxpayers and observe the causes of failures with tax obligations were used, one can conclude that 76% of formal traders do not cancel their tax obligations on time